Study of unsteady loadings on the propeller under steady drift and yaw motion using URANS, hybrid (URANS-LES) and LES methods. Issue 2 (3rd May 2016) - Abbas, N.; Kornev, N.
Abstract : In this paper, results of computations of unsteady wake and unsteady loadings on marine propellers behind KVLCC2 tanker under different drift angles and yaw rates are presented and analysed. Hybrid unsteady Reynolds averaged equations-large eddy simulations (URANS-LES) presented in [Kornev, N., Taranov, A., Shchukin, E. and Kleinsorge, L. 2011. Development of hybrid URANS-LES methods for flow simulation in the ship stern area. Ocean Engineering, 38, pp.1831–8], hybrid IDDES, k-ω SST URANS and pure LES DMM models are utilised. In the first step, the vortex structures, fluctuations of velocity fields in the nominal wake are analysed behind the bare hull. In the second step, the arrangement containing both hull and rotating propeller is computed with consideration of all interaction effects at different drift angles and yaw rate. It was shown that unsteady loadings on propeller increase at non-zero drift angle and yaw rate.